Antigiardial activity of novel triazolyl-quinolone-based chalcone derivatives: when oxygen makes the difference - Bahadur, Vijay; Mastronicola, Daniela; Singh, Amit K.; Tiwari, Hemandra K.; Pucillo, Leopoldo P.; Sarti, Paolo; Singh, Brajendra K.; Giuffrè, Alessandro (Frontiers in Microbiology, 2015)
Giardiasis is a common diarrheal disease worldwide caused by the protozoan parasite Giardia (G.) intestinalis. It is urgent to develop novel drugs to treat giardiasis, due to increasing clinical resistance to the gold standard drug metronidazole (MTZ). New potential antiparasitic compounds are usually tested for their killing efficacy against G. intestinalis under anaerobic conditions, in which MTZ is maximally effective. On the other hand, though commonly regarded as an ‘anaerobic pathogen’, G. intestinalis is exposed to relatively high O2 levels in vivo, living attached to the mucosa of the proximal small intestine. It is thus important to test the effect of O2 when searching for novel potential antigiardial agents, as outlined in a previous study (Bahadur, Mastronicola et al. (2014) Antimicrob. Agents Chemother. 58, 543). Here, forty-five novel chalcone derivatives with triazolyl-quinolone scaffold were synthesized, purified and characterized by high resolution mass spectrometry, 1H and 13C nuclear magnetic resonance and infrared spectroscopy. Efficacy of the compounds against G. intestinalis trophozoites was tested under both anaerobic and microaerobic conditions, and selectivity was assessed in a counter-screen on human epithelial colorectal adenocarcinoma cells. MTZ was used as a positive control in the assays. All the tested compounds proved to be more effective against the parasite in the presence of O2, with the exception of MTZ that was less effective. Under anaerobiosis eighteen compounds were found to be as effective as MTZ or more (up to 3-4 fold); the same compounds proved to be up to > 100 fold more effective than MTZ under microaerobic conditions. Four of them represent potential candidates for the design of novel antigiardial drugs, being highly selective against Giardia trophozoites. This study further underlines the importance of taking O2 into account when testing novel potential antigiardial compounds.